Constructing old age: How Newspapers Use Bias and Persuasion to Shape the Aging Discourse - Holyk, Snizhana (Revue internationale Animation, territoires et pratiques socioculturelles / International Journal of Sociocultural community development and practices / Revista internacional Animación, territorios y prácticas socioculturales)

(untitled) (Département de communication sociale et publique, Université du Québec à Montréal, 2025)
Among the many social issues examined through an ideological framework, aging appears to be particularly significant, with media representations playing a pivotal role in its discursive construction. This paper examines the construal of old age using ideologically charged language and framing strategies in newspaper discourse. Applying the methodology of critical discourse analysis to The Guardian articles, the study illuminates how narratives about aging reflect and reinforce societal norms, cultural assumptions, and policy interpretations. By analyzing the use of expert opinions, older adults’ voices, and intertextual references, the paper identifies dominant themes such as medicalization, economic burden, active aging, and intergenerational tensions. Moreover, the study argues that newspaper discourse not only mirrors public attitudes towards older adults but actively participates in shaping them, privileging certain identities, while marginalizing others.